Eating disorder problem among young adult / Muffidah Hanim Ramly and Isfahani Ishak - Ramly, Muffidah Hanim; Ishak, Isfahani (2012)
Eating disorder has been categorized as a mental health problem and there is a rise in the number of sufferers. It is a serious health conditions that can be both physically and emotionally destructive for females and males. As a result, this situation reflects on the quality future labor force world wide. The aim of this article is to identify the perception of university student towards the factors of eating disorder problem among young adults. Therefore, the reason of this article is to identify what are the relationships between low self-esteem, media influence and peer pressure with eating disorder problem among young adult. It is also to answer the objective whether there are relationships between these three factors with eating disorder. Besides that, the scope of this article covers young adult that is refer to the degree student in four degree courses in UiTM Kedah.